PENDIDIKAN KEWIRAUSAHAAN: KONSEP, KARAKTERISTIK, DAN IMPLIKASINYA TERHADAP KEMANDIRIAN GENERASI MUDA - Nadia Ayu Pradila; Rahmawati Alwi (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2026)
This study discusses the importance of entrepreneurial education as a means to foster independence in the younger generation through formal education. Many believe that entrepreneurship requires innate talent, so not everyone can be involved. However, with limited job opportunities and high unemployment rates, entrepreneurial education becomes a solution to encourage young people to become entrepreneurs. The goal of this education is to build self-confidence, creativity, innovation, and the courage to take risks for individuals who do not possess a natural entrepreneurial spirit. This study explains the concepts, characteristics, and implications of entrepreneurial education in empowering the younger generation, with an emphasis on the role of educators in the process. The method used is a literature review from various academic sources